β-amyloid and Oxidative Stress: Perspectives in Drug Development - Caruso, Giuseppe; Spampinato, Simona F.; Cardaci, Vincenzo; Caraci, Filippo; Sortino, Maria A.; Merlo, Sara (Current Pharmaceutical Design, 2019)
Alzheimer’s Disease (AD) is a slow-developing neurodegenerative disorder in which the main pathogenic role has been assigned to β-amyloid protein (Aβ) that accumulates in extracellular plaques. The mechanism of action of Aβ has been deeply analyzed and several membrane structures have been identified as potential mediators of its effect. The ability of Aβ to modify neuronal activity, receptor expression, signaling pathways, mitochondrial function, and involvement of glial cells have been analyzed. In addition, extensive literature deals with the involvement of oxidative stress in Aβ effects. Herein we focus more specifically on the reciprocal regulation of Aβ, that causes oxidative stress, that favors Aβ aggregation and toxicity and negatively affects the peptide clearance. Analysis of this strict interaction may offer novel opportunities for therapeutic intervention. Both common and new molecules endowed with antioxidant properties deserve attention in this regard.
Keywords: antioxidants